The Realization of Communication Tasks in Negotiating Meaning among EFL learners - Rachma, Nita Sitta; Faridi, Abdurrachman; Rukmini, Dwi (English Education Journal, 2020)
People currently live at a time where the ability to speak English fluently has become a must for those who attempt to advance in certain fields. In classroom context however communication task is considered as a crucial element of English language teaching. As a strategy of communication, negotiation of meaning plays as a process through which the speakers go to clearly comprehend one another. The aims of this study are to analyze the realization of different communication tasks in negotiating meaning and to dig up those tasks in order to explain its impact on negotiation of meaning. A qualitative method is applied in this study where twenty undergraduate students majoring in English Language Education took part in it. The students were paired and assigned to perform five different communication tasks. The result showed that communication tasks had been effectively used as an opportunity for students to elicit the occurrences of negotiation of meaning in interactions. Moreover, it was discovered that each task type yielded different amount of negotiation. Information gap task came out as the most productive task in promoting negotiation of meaning among the other four with some negotiation of meaning strategies employed by students during negotiation; clarification request, confirmation checks, and comprehension checks. In conclusion, engaging students in such communication tasks leading to negotiating meaning helps them in developing their linguistic acknowledgement. It is due to the frequent use of negotiation of meaning strategies can contribute to language development of EFL learners in all level of proficiency.